Santripreneur as an Economic Transition Model for Santri After Pesantren: Entrepreneurship Training Study at Manbaul Ulum - Mursidah; Ahmad Faizal (Universitas Muhammadiyah Ponorogo, 2026)
Introduction/Main Objectives: This study examines the santripreneur model as a strategy for supporting the economic transition of santri after completing their education in pesantren. The topic is important because many pesantren graduates possess strong religious competencies but still face challenges in achieving economic independence and adapting to the demands of the labor market and business sector. As pesantren continue to expand their role as educational and community empowerment institutions, entrepreneurship training has emerged as a strategic approach to strengthening the economic capacity of santri. Background Problems: The main issue addressed in this study is how entrepreneurship training contributes to the development of an effective santripreneur model that supports santri’s economic transition after pesantren. Novelty: The novelty of this research lies in the integration of entrepreneurship education, Islamic economic values, and economic transition within the pesantren context, which has received limited empirical attention in previous studies. Research Methods: This study employs a qualitative case study approach at Manbaul Ulum Pesantren. Data were collected through observation, in-depth interviews, and documentation involving 30 respondents consisting of pesantren administrators, santri participating in entrepreneurship training programs, and alumni who have established businesses after graduation. Findings/Results: The findings indicate that entrepreneurship training enhances entrepreneurial knowledge, practical skills, business attitudes, and self-confidence while strengthening the internalization of Islamic values. The santripreneur model has proven effective in preparing santri to engage in productive economic activities. Conclusion: This study concludes that santripreneur is a promising economic empowerment model for strengthening santri independence and supporting the development of a pesantren-based Islamic economic ecosystem